Does Social Media Use Increase Innovative Work Behavior? The Mediating Role of Digital Engagement - Rizkiya, Cahaya Alya; Rahman, Muhammad Fajar Wahyudi; Amelia, Ratih; Wihara, Dhiyan Septa (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2026)
This study examines the mediating role of digital engagement in the relationship between social media use and innovative work behavior among employees of Perumda Air Minum Surya Sembada Kota Surabaya, specifically within the context of promoting the Customer Information System (CIS) application. Using a quantitative approach with Partial Least Squares–Structural Equation Modeling (PLS-SEM), data were obtained from 70 eligible employees after the data screening process. The findings reveal that social media use positively and significantly influences both innovative work behavior and digital engagement. Furthermore, digital engagement itself demonstrates a significant positive effect on innovative work behavior. Crucially, digital engagement proves to be a significant mediator in the relationship between social media use and innovative work behavior. These results underscore that active digital engagement via social media platforms can effectively foster employee innovation, particularly in supporting organizational digital product promotion. The study strengthens the theoretical framework of Uses and Gratifications (U&G) by highlighting psychological engagement as a key mechanism. Practically, it offers organizations a blueprint for designing digital engagement strategies that enhance employee-driven innovation for digital product advancement.